DECOLONIAL FEMINISM AND DIASPORA: ISSUES OF RACE, CLASS, AND GENDER IN THE POETRY OF RUPI KAUR AND FATIMAH ASGHAR (Contemporary Journal of Social Science Review, 2025)
This paper explores the ways in which poetic works by South Asian women in diaspora incorporate feminist themes that challenge boundaries of race, class and gender defined by colonial frameworks. The study makes an argument for an approach that challenges the Eurocentric feminist and literary canon by drawing on Chandra Mohanty’s “Feminism Without Borders: Decolonizing Theory, Practicing Solidarity.” The theoretical underpinnings provide an intersectional approach to decolonization interlinking issues of race, gender and class as presented in the selected poetry of Rupi Kaur from “the sun and her flowers” and Fatimah Asghar from “If They Come for Us”. The paper argues its way towards amplifying South Asian diasporic voices that represent experiences of marginalized populations and counter the dominance of Western feminism.